The Effect of Andaliman Fruit Extract on the Incision Wound Healing the Wistar Male White Rats and Collagen Type III - Intan Hasibuan, Febria Nurul; Chiuman, Linda; Fachrial, Edy (Jurnal Kesehatan, 2024)
The extract of andaliman fruit has antimicrobial activity. The active compounds of andaliman fruit are believed to positively contribute to human health, one of which is flavonoids, which can improve the wound healing process because of their function as an antioxidant and anti-inflammatory. This study aims to determine the effect of giving ethanol extract of andaliman fruit on the healing process of incision wounds in Wistar strain white rats and collagen type III. This research is an experimental posttest-only controlled group design. This study used five groups: NaCL treatment, betadine treatment, 1% andaliman ethanol extract treatment, 3% andaliman ethanol extract treatment, and 5% andaliman ethanol extract treatment, where each group had six rats. Data analysis used normality tests, homogeneity tests, and ANOVA tests. The results showed that the ethanol extract of andaliman fruit contains several active compounds such as alkaloids, saponins, tannins, and glycosides. The fastest incision wound healing was the fourth test group, the test group with 3% andaliman fruit ethanol extract treatment on day 14, with an average length of incision wound healing of 3.44mm. The 3% andaliman ethanol extract had the potential to accelerate wound healing activity.